The character table for the corepresentations of magnetic groups - Newmarch, J.D.; Golding, R.M. (AIP Publishing, 1982)
A square character table is shown to exist for all finite magnetic groups. The table possesses row and column orthogonality properties similar to the character table for linear groups.